Understanding Violent Religious Behavior in Indonesia; From the Concept to the Prevention - Dana Riksa Buana; Oleg Valeryevich Lukyanov (Jurnal Cita Hukum, 2020)
AbstractOne of the social issues that are developing rapidly in Indonesia today is violent religious behavior. Several terms are used to describe such behavior as fundamentalism, radicalism, extremism, or terrorism. The government and the authorities are trying to prevent and eradicate this problem, but it will not be effective if the four concepts above are still used ambiguously by the mass media and scientific journals. Therefore, this article will explain these constructs elaborately so that the eradication of violent religious behavior can be done accurately. The method for this research uses a normative juridical method that examines references or secondary data as a basis for the analysis by searching the literature relating to the problem under study. The results and discussion of the research explain that extremism and radicalism are the seeds of the birth of criminal acts of terrorism, while fundamentalism is how an individual feels belonging to a religion and thus considers that his belief is the most right faith and ready to defend it. Besides, this paper will also analyze what factors are the causes of extreme religious actions, as well as how to handle them psychologically (internally) and interventions from government and society (external).Keywords: Violent Religious Behavior; Fundamentalism; Religious Identity, Spirituality AbstrakSalah satu masalah sosial yang berkembang pesat di Indonesia saat ini adalah perilaku agama yang penuh kekerasan. Beberapa istilah digunakan untuk menggambarkan perilaku seperti fundamentalisme, radikalisme, ekstremisme, atau terorisme. Pemerintah dan pihak berwenang berusaha mencegah dan memberantas masalah ini, tetapi itu tidak akan efektif jika keempat konsep di atas masih digunakan secara ambigu oleh media massa dan jurnal ilmiah. Oleh karena itu, artikel ini akan menjelaskan konstruksi tersebut secara rumit sehingga pemberantasan perilaku keagamaan yang keras dapat dilakukan secara akurat. Metode penelitian ini menggunakan metode yuridis normatif yang meneliti referensi atau data sekunder sebagai dasar analisis dengan mencari literatur yang berkaitan dengan masalah yang diteliti. Hasil dan diskusi penelitian menjelaskan bahwa ekstremisme dan radikalisme adalah benih kelahiran tindak pidana terorisme, sementara fundamentalisme adalah bagaimana seorang individu merasa menjadi bagian dari sebuah agama dan dengan demikian mencerminkan bahwa keyakinannya adalah keyakinan yang paling benar dan siap untuk mempertahankan Itu. Selain itu, makalah ini juga akan menganalisis faktor-faktor apa yang menjadi penyebab tindakan keagamaan yang ekstrem, serta bagaimana menanganinya secara psikologis (internal) dan intervensi dari pemerintah dan masyarakat (eksternal).Kata kunci: Perilaku Agama yang Penuh Kekerasan; Fundamentalisme; Identitas Agama, Spiritualitas  АннотацияОдной из социальных проблем, которая быстро развивается в Индонезии в настоящее время, является насильственное религиозное поведение. Несколько терминов используются для описания такого поведения: фундаментализм, радикализм, экстремизм или терроризм. Правительство и органы власти пытаются предотвратить и искоренить эту проблему. Однако, попытка не будет эффективной, если четыре вышеуказанные концепции все ещё будут двусмысленно использоваться средствами массовой информации и научными журналами. Таким образом, эта статья подробно объяснит эти конструкции, так что искоренение насильственного религиозного поведения может быть сделано в точности. Метод данного исследования является нормативным юридическим, который рассматривает ссылки или вторичные данные в качестве основы для анализа путем поиска литературы, относящейся к изучаемой проблеме. Результаты и обсуждение исследования объясняют, что экстремизм и радикализм являются семенами рождения преступных террористических актов, в то время как фундаментализм - это то, как человек чувствует принадлежность к религии и, таким образом, считает что его вера является самой правильной и готов защищать её. Кроме того, в этой статье будет проанализировано, какие факторы являются причинами экстремальных религиозных действий, а также как справиться с ними психологически (внутренне) и с помощью вмешательства со стороны правительства и общества (внешне).Ключевые слова: насильственного религиозного, Индонезии